ChemInform Abstract: Silver‐Catalyzed Decarboxylative Radical Azidation of Aliphatic Carboxylic Acids in Aqueous Solution. Issue 3 (29th December 2015) - Liu, Chao; Wang, Xiaoqing; Li, Zhaodong; Cui, Lei; Li, Chaozhong
Abstract: An efficient and general method for the decarboxylative azidation of aliphatic carboxylic acids is reported.